A molecularly-imprinted SERS sensor based on a TiO2@Ag substrate for the selective capture and sensitive detection of tryptamine in foods. (15th November 2022) - Chen, Chen; Wang, Ximo; Zhang, Yingfang; Li, Xingying; Gao, Huiju; Waterhouse, Geoffrey I.N.; Qiao, Xuguang; Xu, Zhixiang
Highlights: A sensitive, rapid and selective SERS sensor for tryptamine was developed. The TiO2 @Ag@MIP sensor used TiO2 NPs and Ag NPs for signal-amplification. Adding a molecularly imprinted polymer enabled selective tryptamine recognition. The sensor's linear range was 10 −6 –10 −2 mol L −1, with a LOD of 4.85 × 10 −7 mol L −1 . The developed sensor allowed tryptamine quantification in a variety of foods. Abstract: Herein, a molecularly imprinted surface-enhanced Raman spectroscopy (SERS) sensor was developed for the selective capture and sensitive detection of tryptamine in foods. The SERS sensor exploited silver nanoparticle-decorated TiO2 (TiO2 @Ag) substrates for Raman signal enhancement via synergistic effect of electromagnetic enhancement and photoinduced charge-transfer, whilst surface functionalization with the molecularly imprinted polymer ensured selective tryptamine capture. The SERS spectrum of tryptamine on the sensor closely matched that predicted by density functional simulations. The SERS intensity for tryptamine on the developed TiO2 @Ag@MIP sensor increased linearly with the logarithm of the tryptamine concentration over the range of 10 −6 –10 −2 mol L −1, with a LOD of 4.85 × 10 −7 mol L −1 . Tryptamine was detected in a spiked white vinegar sample, and its recoveries were in the range of 92.00%–111.40%. The SERS sensor could be used for the detection of tryptamine in actual samples.